Estimation of thrusts generated by each body part during underwater dolphin kick using "SWUM" - Sugimoto, S.; Nakashima, M.; Ichikawa, H.; Nomura, T. (Biomechanics and Medicine in Swimming X, 2006)
It is important to understand the dynamics of the entire human body during swimming, but measurement of the fluid force of a self-propelled human body is extremely difficult. A simulative model of human swimming "SWUM" (SWimming hUman Model) incorporates dynamics of the entire human body. This study is intended to use the Simulation model to calculate the thrust generated by each body part during under-water dolphin kick. First, an outline is described for the Simulation model. Second, the methods of measuring input data for the Simulation model are described. Third, methods to recreate dynamics on the Simulation are described. Consequently, the dynamics of the underwater dolphin kick were recreated through the Simulation. Results showed that the feet mainly generate thrust during the underwater dolphin kick. Furthermore, both increased thrust and drag are important for faster swimming because greater thrust generates greater drag.